(untitled) (Acta Entomológica Chilena, 2022)
Cotesia marginiventris (Cresson) (Hymenoptera: Braconidae), is one of the most important parasitoid species of the natural enemy complex atacking Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) in soybean crops in Buenos Aires Province, Argentina. The objective of this study was to analyze the parasitism, survivorship, sex ratio and developmental time of C. marginiventris. Two R. nu generations were sampled in crops in Buenos Aires Province during the growing seasons of 1992 and 1993, and only one in 1994. Percentage parasitism was: 32.3% and 20% in 1992; 32.6% and 40% in 1993; and 43.9% in 1994. Cumulative percentage parasitism for the first and second generation was:21%and 19,3% in 1992; 13.7% and 35.7% in 1993; and 24.4% the only generation in 1994. Parasitoid mortality affected mainly the pupal stage. Sex (male: female) ratio was (1:1.5). Mean developmental time from host collection (larvae < 1.5 cm length) to adult parasitoid emergence was 7.89 +- 2.26 days (27 +- 1°C; 70% HR; 16:8 L:D).